Bone regeneration around implants with modified surface by acid conditioning with the fluoride ions deposition - De Souza, A. S.; Colombo, L. T. [UNESP]; Hadad, H. [UNESP]; Santos, A. F.P. [UNESP]; Capalbo-Silva, R. [UNESP]; Poli, P. P.; Elias, C. N.; Vedovatto, E.; Souza, F. A. [UNESP]; Carvalho, P. S.P. [UNESP] (My University, 2020)
Aim: Evaluate the late bone regeneration around implants with machined (MS) and acid modified surfaces followed by the deposition of fluoride ions (AFS) in the tibiae of rabbits. Materials and methods: Ti-cp disks and implants underwent the topographic characterization before surgery through scanning electron microscope, x-ray energy dispersive spectrometer (SEM-EDX), roughness average (Ra) and, cross section. Six rabbits received 12 implants in their tibiae. After 12 weeks, euthanasia was performed. The percentage of bone interface contact (BIC%) and neoformed bone area (NBA%) was measured. Data were submitted to the statistical analysis. Results: SEM-EDX revealed smooth surface, contaminated with machining residues and peaks of Ti for MS group and AFS group, peaks and valleys with presence of Ti, O, Na, Cl and F. Ra showed statistical difference between AFS (1.34 ± 0.35 μm) than MS (0.4 ± 0.06 μm). Cross section showed a mean thickness of 7.84 ± 3.73 μm for ASF and 1.26 ± 0.55 μm for MS. The mean values of BIC% for AFS were statistically higher than MS. For NBA% there is no statistical difference between grups. Conclusions: The surface modified by acid conditioning followed the addition of fluoride ions provides superior osseointegration process, even in the later periods of bone regeneration.
Keywords: Bone regeneration; Bone-implant interface; Dental implants; Fluorine; Titanium